A preliminary study of the clinical differences between dissociative and nondissociative depression in Hong Kong: implications for mental health practice. (3rd July 2019) - Fung, Hong Wang; Chan, Chitat
ABSTRACT: Depression is a serious public health issue, but not all patients with depression respond well to pharmaceutical treatments. Some scholars suggested that dissociation could be a marker indicating the types of patients with depression that may benefit more from psychosocial interventions than from pharmaceutical treatments. This study explored the possibility to differentiate dissociative depression and nondissociative depression in a clinical sample ( N = 68) in the Chinese context, and discusses the potential implications for treatment considerations. Compared with the nondissociative group, the dissociative group reported higher occurrences of psychosocial etiological risk factors (e.g., childhood physical abuse, lack of help from family) and psychosocial-related symptoms (e.g., unstable relations, fear of abandonment, trauma-related flashbacks, somatization symptoms). Our initial findings revealed that patients with dissociative depression appeared to have distinct clinical features and might require more psychosocial interventions. Implications for health care research and practice are discussed.